Camila the dancing star - Salazar, Alicia, 1973- (Salazar, Alicia, 1973- Camila the star., 2022)
At dance camp Camila teams up with new friends Lulu and Raisa and they enter the dance competition Las Estrellas; but when Camila injures her ankle it looks like they are out of the contest--until Raisa suggests they perform a sitting dance from India.